ANKLE BRACE ATTENUATES THE MEDIAL-LATERAL GROUND REACTION FORCE DURING BASKETBALL REBOUND JUMP - Castro, Alex [UNESP] (2017)
Introduction: The jump landing is the leading cause for ankle injuries in basketball. It has been shown that the use of ankle brace is effective to prevent these injuries by increasing the mechanical stability of the ankle at the initial contact of the foot with the ground. Objective: To investigate the effects of ankle brace on the ground reaction force (GRF) during the simulation of a basketball rebound jump. Method: Eleven young male basketball players randomly carried out a simulated basketball rebound jump under two conditions, with and without ankle brace (lace-up). Dynamic parameters of vertical GRF (take-off and landing vertical peaks, time to take-off and landing vertical peaks, take-off impulse peak, impulse at 50 milliseconds of landing, and jump height) and medial-lateral (take-off and landing medial-lateral peaks, and time to reach medial-lateral peaks at take-off and landing) were recorded by force platform during rebound jumps in each tested condition. The comparisons between the tested conditions were performed by paired t test (P<0.05). Results: The use of ankle braces reduced the medial and lateral peaks of the GRF by -15.7% (P=0.035) and -24.9% (P=0.012), respectively, during the landing of the rebound jump. Additionally, wearing the brace did not affect any dynamic parameters of vertical GRF or temporal parameters of the medial-lateral GRF (P>0.05). Conclusion: The use of ankle brace during basketball rebound jumps attenuates the magnitude of medial-lateral GRF on the landing phase, without changing the vertical GRF. This finding indicates that the use of brace increases the medial-lateral mechanical protection by decreasing the shear force exerted on the athlete's body without change the application of propulsive forces in the take-off and the impact absorption quality in the landing during the basketball rebound jump.